A 5th/11th century chronicler from Tripoli. (November 2022) - Montel, Aurélien
Abstract: It is generally believed that Tripolitanian historiography began with the chronicle of Muḥammad b. Ghalbūn in the first half of the 12th century AH/18th century AD, before expanding in the 13th/19th. This pattern tends to forget that other players – unfortunately now lost – predated that modern historical writing. The oldest one seems to be related to a Tripolitanian scholar, ʽAlī b. ʽAbd Allāh b. Maḥbūb al-Ṭarābulusī, who lived at the end of the 5th/11th century/beginning of the 6th/12th, who settled in the East and wrote a short chronicle to give an account of the history of his hometown. This article aims to gather all the data related to him and his works, to show the formation of a local memory in the wake of the political autonomy acquired by Tripoli from the beginning of the 5th/11th century.